Cyclic use of saline and non-saline water to increase water use efficiency and soil sustainability on drip irrigated maize in a semi-arid region - Hassanli, Mohammad; Ebrahimian, Hamed (Spanish journal of agricultural research : SJAR, 2016)
Use of saline water for irrigation is a strategy to mitigate water shortage. The objective of this study was to investigate the impact of the cyclic and constant use of saline and non-saline water on drip irrigated maize yield and irrigation water use efficiency (IWUE). Nine field treatments were laid out based on alternative irrigation management of non-saline and saline water combinations. The treatments were: two salinity levels of 3.5 and 5.7 dS/m and freshwater (0.4 dS/m) application in every one, three and five saline water application (1:1, 3:1 and 5:1, respectively). Results showed that the 1:1 combination management was the best in terms of crop yield and IWUE. In this treatment, salt concentration at the end of growing season was not significantly changed compared to its initial condition. If off-season precipitation or leaching was available, the 3:1 and 5:1 treatments were appropriated. Highest and lowest values of IWUE were 15.3 and 8.7 kg/m3 for the 1:1 management using water salinity of 3.5 dS/m and the treatment of constant irrigation with water salinity of 5.7 dS/m, respectively. Under low off-season precipitations, artificial leaching is essential for land sustainability in most treatments.